Vineyard or olive garden: an investment decision. Issue 2 (31st May 2022) - Riaz, Yasir; Abdullah, Iqra
Abstract : Learning outcomes: The learning outcomes are as follows: demonstrate an understanding of the fruit farming process; compare the pros and cons of farming different fruits; understand the general characteristics of entrepreneurs and identify the issues they face; compare the risk and returns from two types of investments; apply capital budgeting techniques to ascertain the best available investment option; and perform sensitivity analysis based on different anticipated situations for a new business. Case overview/synopsis: Since his birth, Mr Bashir Khan, a 45-year-old father of four, lived as a farmer in Kallar Kahar, Pakistan. He owned 15 acres of land which he used to cultivate wheat and millet. He decided to start fruit farming after harvesting wheat in April 2021 to satisfy his long-standing desire to own a garden. He recently met a friend who was earning well from grape farming, who suggested that Khan set up a vineyard farm which could become a profitable venture for him. At the same time, Khan learned that the government had declared the Potohar region of Pakistan an olive valley, and was giving massive subsidies on olive cultivation. Khan now had a choice of fruits to plant on his land. One of his relatives, Omar Khayam, was an accountant at a firm. Khayam offered to conduct a feasibility analysis for Khan, to provide the relevant data, and help Khan select a high profit-yielding fruit farm. Complexity academic level: Introductory finance courses at the undergraduate and postgraduate levels as well as executive training courses focused on the agri-finance discipline. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 1: Accounting and Finance.